Implementing the STEM Approach in High School: Challenges and Opportunities in Renewable Energy Learning - Ginting, Fajrul Wahdi; Sakdiah, Halimatus; Unaida, Ratna; Idris, Syafrizal; Fakhrah, Fakhrah (Electronic Journal of Education, Social Economics and Technology, 2025)
Renewable energy learning in senior high schools has significant potential to be developed through a STEM approach; however, its implementation in classroom practice remains limited. This study aimed to explore the implementation of STEM learning in senior high schools on renewable energy topics, identify the challenges encountered, and examine the opportunities for developing project-based STEM learning. A mixed-method approach with a descriptive exploratory design was employed. The research subjects consisted of 30 science teachers and 617 senior high school students from several schools in Lhokseumawe City and North Aceh Regency. Data were collected through closed and open-ended questionnaires and document analysis of lesson plans, teaching modules, and student worksheets, and analyzed using descriptive statistics and thematic analysis. The results revealed that STEM learning implementation was at a moderate and partial level, with STEM components not yet explicitly integrated. Major challenges included limited pedagogical understanding of STEM, inadequate facilities, time constraints, and difficulties in project assessment. Nevertheless, high student interest, local contextual potential, and curriculum support indicate substantial opportunities for developing project-based STEM learning on renewable energy topics. This study provides an evidence-based foundation for the development of contextual and sustainable STEM-based renewable energy learning in senior high schools.